National Trends of Antiparkinsonism Treatment in Taiwan: 2004–2011 - Weng-Ming Liu; Ruey-Meei Wu; Chia-Hsuin Chang; Jou-Wei Lin; Ying-Chun Liu; Chin-Hsien Lin (Parkinson's Disease)
Background. Several guidelines for Parkinson’s disease (PD) management were recently updated. We examined temporal trends for antiparkinsonism drugs in Taiwan. Methods. Antiparkinsonism prescriptions, including levodopa, ergot/nonergot dopamine agonists (DAs), amantadine, selegiline, entacapone, and anticholinergics, were identified in the Taiwan National Health Insurance Database from 2004 to 2011. Time trend analyses were estimated assuming Poisson distribution. Results. A total of 19,302 PD patients in 2004 and 41,606 PD patients in 2011 were analyzed. Antiparkinsonism prescriptions increased significantly from 187,137 in 2004 to 414,587 in 2011. Levodopa monotherapy or combination therapy was the mainstay. Levodopa monotherapy comprised 37.4% of prescriptions in 2004 and 44.2% in 2011, with an annual increase rate of 18.14%. There was a substantially increasing trend of DA prescriptions, which were higher in younger-aged patients (<60 years) than in older-aged group (p=0.0006). Among combination therapy, DA combined with levodopa or other antiparkinsonism medications became the main combinations for younger-aged patients after 2009. After 2005, the proportion of ergot DA usage markedly decreased and PD patients using nonergot DA increased. Conclusions. Levodopa was the major treatment from 2004 to 2011. There was a steeply increased trend of DA use, especially in younger-aged patients. Nonergot agents comprised the major DA group after 2005.